The diagnostic utility of INSM1 and GATA3 in discriminating problematic medullary thyroid carcinoma, thyroid and parathyroid lesions - Adel Hakim, Sarah; Mohamed Abd Raboh, Nermine (Polish Journal of Pathology, 2021)
Discriminating thyroid and parathyroid lesions may sometimes pose a diagnostic difficulty. Medullary thyroid carcinomas (MTCs) display various cytologic and architectural features that resemble other thyroid and even rarely some parathyroid neoplasms. Moreover, some MTCs may have negative serum calcitonin, rendering them difficult to diagnose. Hence, to reach an appropriate diagnosis in problematic cases of these three categories – thyroid lesions, MTC and parathyroid lesions – the use of several immunohistochemical panels has been suggested and applied. However, conventional markers are not always conclusive in problematic cases. Thus, in the current study we aim to evaluate the diagnostic utility of using GATA3 and INSM1 (insulinoma-associated protein 1) as novel nuclear markers to be applied as an adjunct in case of histopathologic suspicion. A retrospective study was carried out on samples of lesions from three groups: group 1: thyroid lesions (27), group 2: medullary thyroid carcinoma (25); 1/25 had negative serum levels of calcitonin, and group 3: parathyroid lesions (36). Biopsies were received at the Pathology Laboratory of Ain Shams University Hospitals. INSM1 showed 98% diagnostic accuracy in diagnosing MTC and differentiating it from other thyroid lesions. The case of MTC with negative serum calcitonin showed positive INSM1 staining. GATA3 showed 96.8% diagnostic accuracy in diagnosing parathyroid lesions and differentiating them from thyroid lesions. Using immunohistochemical staining by GATA3 and INSM1, in the appropriate histopathological setting, significantly aids in the differentiation between thyroid lesions, parathyroid lesions and MTCs. INSM1 could serve as a potential diagnostic marker in the rare cases of non-secretory MTC and in metastatic work up.